2014
DOI: 10.1007/s00265-014-1786-8
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen-associated self-medication behavior in the honeybee Apis mellifera

Abstract: Honeybees, Apis mellifera, have several prophylactic disease defense strategies, including the foraging of antibiotic, antifungal, and antiviral compounds of plant products. Hence, honey and pollen contain many compounds that prevent fungal and bacterial growth and inhibit viral replication. Since these compounds are also fed to the larvae by nurse bees, they play a central role for colony health inside the hive. Here, we show that honeybee nurse bees, infected with the microsporidian gut parasite Nosema ceran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
92
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 55 publications
5
92
1
Order By: Relevance
“…In these laboratory studies, test bees were heavily (experimentally) infected with Nosema spores (10 5 –3.3 × 10 5  spores/bee) followed by an artificial maintaining of bees in small cages. In the current study, only naturally occurring infections were monitored and infected bees could potentially perform self-medication behavior (Gherman et al 2014) or outside activities to limit contact in the hive with nest mates (Alaux et al 2014). In this respect, a detail of the study of Pettis et al (2012) is worth mentioning.…”
Section: Discussionmentioning
confidence: 99%
“…In these laboratory studies, test bees were heavily (experimentally) infected with Nosema spores (10 5 –3.3 × 10 5  spores/bee) followed by an artificial maintaining of bees in small cages. In the current study, only naturally occurring infections were monitored and infected bees could potentially perform self-medication behavior (Gherman et al 2014) or outside activities to limit contact in the hive with nest mates (Alaux et al 2014). In this respect, a detail of the study of Pettis et al (2012) is worth mentioning.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Gherman et al (2014) showed honey type-specific spore load reduction for N. ceranae . They suggested multiple nonexclusive mechanisms that might be important: The active compounds may (1) kill Nosema spores, (2) increase the activity of the honeybee immune system to fight against microsporidian infections, or (3) inhibit the replication of vegetative forms of Nosema spp.…”
Section: Honeymentioning
confidence: 99%
“…They suggested multiple nonexclusive mechanisms that might be important: The active compounds may (1) kill Nosema spores, (2) increase the activity of the honeybee immune system to fight against microsporidian infections, or (3) inhibit the replication of vegetative forms of Nosema spp. Whatever the actual mechanisms, those specific honey types that resulted in a reduction of a N. ceranae spore load had also been selected in a choice assay by workers infected with N. ceranae but not by healthy bees, suggesting a self-medication potential of honey at the level of the individual bee (Gherman et al 2014).…”
Section: Honeymentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, animals that consume antimicrobial phytochemicals may gain protection from their own parasites, as shown in herbivores161718. In pollinators, ingestion of floral phytochemicals19 and certain types of honey20 were therapeutic for infected honey bees ( Apis mellifera ). Infection also stimulated collection of phytochemical-rich resins21 and preference for high-phytochemical nectar2223, indicating the potential for phytochemicals to improve pollinator health.…”
mentioning
confidence: 99%